PEMBERIAN ULTRASOUND DAN STRECHING PADA PELARI REKREASIONAL DENGAN PLANTAR FACITIS DI KLINIK UTAMA MOTIVA - Agis Ardiani (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. Depression is widespread among adolescents and seriously harms students' quality of life and academic performance. To defend yourself in overcoming stress, you can use physical exercise. This research aims to determine the effect of physical exercise on stress levels in office working mothers. The research method with a literature review was carried out using the PICO search on the Google Scholar database. This shows that the more often physical exercise is carried out by students, the lower the stress level will be, the better the quality of life and academic performance will be, so that there is an influence of physical exercise on reducing stress levels in students due to doing physical exercise when they have a lot on their minds. and stress is able to reduce thoughts and felt stress. The results of the analysis show that physical exercise has a positive effect on reducing stress in students. In Indonesia itself there is no clear prevalence of Plantar Faciitis cases, but one hospital in Jakarta stated that the frequency of patients with complaints of heel pain and Plantar Faciitis was 55.4%, and 22% in the runner population. Motiva is one of the sports health clinics in Jakarta where almost all of the patients are runners with sports-related injuries and plantar faciitis is the second most common after ankle cases. Treatment for Plantar Faciitis consists of physical therapy such as Massage, Mobilization, Ultrasound, Tens, and Taping as well as Stretching. It also has healing success and is often used in Plantar Faciitis programs. Objective: Find out more about the purpose of providing ultrasound and stretching to runners with plantar fasciitis at the Motiva Main Clinic. Method: This research uses a case study where the sample consists of 3 samples of patients who are included in the category of Runners with Plantar Faciitis with intervention 2-3 times per week for 8 meetings. Conclusion: Providing Ultrasound and Active Stretching can reduce pain and improve function in runners diagnosed with Plantar Faciitis.